2006
DOI: 10.1007/s10886-006-9204-y
|View full text |Cite
|
Sign up to set email alerts
|

More Rare Males in Ostrinia: Response of Asian Corn Borer Moths to the Sex Pheromone of the European Corn Borer

Abstract: A previous flight tunnel study showed that 3-5% of European corn borer (ECB) moths, Ostrinia nubilalis (Z/E11-14:OAc), could fly upwind and make contact with sources releasing the sex pheromone of the related Asian corn borer (ACB), Ostrinia furnacalis (2:1 Z/E12-14:OAc). In this study, we show that rare males (3-4%) are also present in South Korean ACB that respond to the sex pheromone blends of the ECB UZ (97:3 Z/E11-14: OAc) and BE (1:99 Z/E11-14:OAc) pheromone races. We also show that the upwind flight res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 25 publications
(47 reference statements)
2
15
0
Order By: Relevance
“…Sex pheromone communication systems may be a major force that drives moth speciation by causing behavioral reproductive isolation via assortative meeting and mating of conspecific individuals (Linn et al 2007). In this study, we found differences in sex pheromone communication between susceptible and two insecticide resistant strains of DBM, and we showed that the differences led to an assortative or preferential mating between different strains.…”
Section: Discussionsupporting
confidence: 48%
“…Sex pheromone communication systems may be a major force that drives moth speciation by causing behavioral reproductive isolation via assortative meeting and mating of conspecific individuals (Linn et al 2007). In this study, we found differences in sex pheromone communication between susceptible and two insecticide resistant strains of DBM, and we showed that the differences led to an assortative or preferential mating between different strains.…”
Section: Discussionsupporting
confidence: 48%
“…Monitoring stem borer populations with pheromones has developed into a mainstay in forecasting for the rice stem borer, Chilo suppressalis (Walker) (Sheng et al 2003;Chen et al 2003Chen et al , 2007, and Asian corn borer (Hu and Jiang 1995, Liu and Zhang 2006, Linn et al 2007. In 2010, pheromone trap captures became the primary technique for timing control applications in NE China.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are “rare” Ostrinia males (3–5%) that possess the ability to respond to a pheromone blend which is not effective for most individuals in the population [15], [40][41]; moreover, significant differences in olfactory neuron responsiveness have been observed between rare and normal males [42][43]. Tandemly arrayed genes are thought to be subject to birth-and-death evolution, in which new genes are created by duplication.…”
Section: Discussionmentioning
confidence: 99%